Managing Volatility in Low-Income Countries : The Role and Potential for Contingent Financial Instruments. (Policy Papers; Policy Paper, 2011)
The paper examines the case for contingent financial instruments for low-income countries (LICs), from both the market and official sector. These include commodity price hedging instruments, contingent debt instruments (commodity-linked bonds, deferred repayment loans), and natural disaster insurance, for example. The paper considers the adequacy of the existing framework of ex post and ex ante support to LICs facing exogenous shocks, and examines the need for and possible constraints to greater availability of contingent instruments. Would there be a role for the international community, particularly the IMF and World Bank, in helping to address the constraints that limit development and use of these instruments?